(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
SADI operation, being simpler in technical execution and quite safe in terms of development of early and remote postoperative complications, can be more often used as a primary operation in the presence of MO, and also performed on patients with super obesity.